INFLUENCE OF CONTACTOR CONTACT PRESSURE IN POWER CIRCUITS OF ELECTRIC STOCK ON THEIR PLASTIC DEFORMATION AND FUSING - Baliichuk, O. Y.; Dubynets, L. V.; Marenych, O. P.; Ustymenko, D. V. (Science and Transport Progress, 2017)
Purpose. The work is aimed at conducting the study to obtain the results that will quantify the influence of contactor contact pressure in power circuits of electric stock on the highest current value Id, that does not cause plastic deformation of contacts; and on the current value Ifs– incipient fusion of contacts taking into account the operation conditions. Therefore, such a study targeted to establish the contact fusing causes is relevant. Methodology. The paper proposes an engineering method for determining the currents Id and Ifs, taking into account the value of contact pressure, electrodynamic forces of contact repulsion Fe.d.r, as well as the pressure influence on the values of such forces. Findings. Taking the contactors 1SVAD8 (locomotive ChS8) and 7SP1 (locomotive ChS4) as an example, the authors conducted the calculations and found that the peak pressure force increases the currents Id and Ifs for these contactors by 11.8%; 15.5%; 11.8%; and 15.4% respectively (compared with the specified currents at the minimum pressure force). Influenced by Fe.d.r the pressure force of contacts for 1SVAD8 contactor decreased by 13.8…31.8%, and for 7SP1contactor the value Fe.d.r may be greater than the pressure force. This can lead to spontaneous shutdown of the closed contactor that is not provided by the control circuit. Ensuring during operation the maximum allowable pressure force of the contacts Fc slightly affects the value Fe.d.r, compared with the case when Fc has the minimum permissible value (in event of a fault in the heating circuit Fe.d.r for contactors 1SVAD8 and 7SP1 is reduced by only 2.45% and 2.59% respectively). Originality. The authors for the first time presented a quantitative assessment of influence of contactor contact pressure in power circuits of electric stock on their plastic deformation and fusing using the proposed engineering method. Practical value. The results obtained during the research allow solving the problem for developing measures aimed to improve the reliability of the heating circuits of electric locomotives ChS8 and ChS4. The proposed method of determining Id and Ifs can be used to quantify the influence of pressure of the main electric contacts mounted in power circuits of electric stock of all series, if during the operation there are cases of plastic deformation, fusing, welding of such contacts, in order to improve the reliability of power circuits.